The role of stem cell therapy in endodontics and its future - Aljifan, Mohammad Khaled; Alshuwayi, Abdulrhman Ali; Almatrafi, Abdulaziz Saeed; Shukr, Abdulelah Mohammed; Alshahrani, Khalid Abdullah; Almuhanna, Abdullah Abdulelah; AlMuhanna, Mohammed Abdullah; Alshammari, Khalid Nasser; Alghamdi, Ahmed Abdullah; Albahri, Mazen Dhafer; Benten, Muath Muhammad (International Journal Of Community Medicine And Public Health, 2022)
Regenerative therapy has been introduced in the literature for a long time and is currently being practiced in different fields, including dentistry and endodontics. Many applications have been reported in the literature for stem cell therapy. However, many complications and adverse events were reported in this context. The present literature review sheds more light on the clinical applications of stem cell therapy in regenerative endodontics and the future perspectives in this field. There are no doubts that there are many questions to be answered despite the huge advances in this field. In response to tissue injury, it has been shown that stem cell therapy can strengthen the efficacy of physiological response to these events and improve tissue regeneration. They can be used for managing cases of reversible pulpitis. Moreover, evidence indicates that they can enhance the revascularization of necrotic pulp tissues. Accordingly, these outcomes can significantly change the perspectives of clinical endodontic practice, and current root canal management modalities and perhaps draws researchers into discovering further future applications for other currently untreatable conditions. However, further future investigations are still needed to understand more about the mechanisms of these modalities and improve their clinical applicability.